Optimizing the Non-Cash Food Assistance Program in Kanrung Village, Central Sinjai District, Indonesia - Syamsiah Hasyim; Khairul Insan; Usnidah Umar; Fajar, Fajar (Tinta Emas Institute, 2025)
This study aims to examine the implementation and impact of the Non-Cash Food Assistance Program (BPNT) in Kanrung Village, Central Sinjai District. This research uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results showed that the implementation of the BPNT program in Kanrung Village showed high effectiveness in terms of implementation and impact on community welfare. A supportive bureaucratic structure and good coordination between various related parties contributed to the program's success. The program's positive impacts, such as reduced economic burden and improved household budget management, confirm that the BPNT program provides significant benefits to the community. This study makes a theoretical contribution in deepening the understanding of the implementation and impact of non-cash food assistance programs in villages. In addition, it practically provides recommendations for kanrung village in optimizing the Non-Cash Food Assistance program in kanrung village.